Metodologi Penelitian Kualitatif / M. Djunaidi Chony, Fauzan Almanshur; editor, Rina Tyas Sari - DJUNAIDI CHONY, M. 1944-; Fauzan Al Manshur; Rina Tyas Sari (Ar-Ruzz Media, 2012)
386 hlm. : ilus. ; 25 cm.